The effect of education using the emo demo ATIKA (Ati Telur Ikan - Liver Egg Fish) method on knowledge about anemia among pregnant women in Bantul Regency - Janah, Anisa Laili; Pratiwi, Arantika Meidya; Fatimatasari, Fatimatasari; Lestari, Prasetya; Rafida, Salsabil Priladiya (Alma Ata University Press, 2025)
Background: Anemia in pregnant women has remained a global health challenge, with a prevalence of 27.7% in Indonesia (SKI 2023), and the highest number of cases in Bantul Regency was found at Sewon II Public Health Center. Anemia in pregnant women is generally caused by increased requirements for iron, vitamin B12, and folic acid during pregnancy. This condition occurs because the mother's blood volume increases by about 20–30%, so the body needs more hemoglobin, which is formed from these nutrients. Poor nutritional understanding and low adherence to iron tablet consumption were the main contributing factors, thus requiring innovative educational approaches such as the Emo Demo ATIKA method (Liver, Egg, Fish) to raise nutritional awareness among pregnant women. Objectives: to determine the effect of education using the emo demo atika method on knowledge about anemia in pregnant women in Bantul Regency.Methods: This study employed a quasi-experimental design with a pretest-posttest nonequivalent control group involving 86 pregnant women in their second and third trimesters, divided into an intervention group (Emo Demo ATIKA) and a control group (lecture method). Data were analyzed using the Wilcoxon and Mann-Whitney tests. Results: The results showed a significant increase in knowledge in both groups after the education (p = 0.001), with a higher improvement in the intervention group, and a significant difference between the two groups (p = 0.001). Conclusions: Therefore, the Emo Demo ATIKA method was proven to be more effective than conventional method in increasing pregnant women's knowledge about anemia and is recommended as an innovative educational tool in healthcare facilities.